Management of Metachronous Bilateral Testis Cancer in a Patient with Pre-B Cell ALL. (3rd February 2015) - Harris, Kelly T.; Shaikh, Shakil A.; Ball, Mark W.; Allaf, Mohamad E.; Pierorazio, Phillip M.
Abstract : We present a patient with a metachronous, second testicular cancer after being diagnosed with pre-B cell ALL and receiving induction chemotherapy for a bone marrow transplant. We discuss the management of bilateral testis masses in a young patient with a hematologic malignancy as well as the role of immunosuppressive chemotherapy in developing a second cancer. This case illustrates the importance of recognizing bilateral testicular cancer early, as well as the importance of follow-up care in oncology patients including routine measurements of tumor markers. A multidisciplinary approach between medical oncology and urology, including close monitoring of the contralateral testis, remains paramount to patient care.